Single-camera full-range high-resolution spectral domain optical coherence tomography - Bo, En (2017)
We developed spectral domain optical coherence tomography using a dual-channel spectrometer for complex conjugate artifacts (CCA) suppression. We used a three-line charge coupled device to simultaneously detect two interferometric spectra with 2 /32π/3 phase difference. The complex interferometric signal was reconstructed by trigonometric manipulation of two real interferometric spectra, and then full-range images were obtained by use of inverse Fourier transform. Artifacts at direct current (DC) and the ghost remnant of the CCA are common issues with the previously reported two-spectrometer method because the slight mismatching between two spectral detection channels had strong negative effects on CCA suppression and appeared to be the limiting factor on system performance. This novel dual-channel spectrometer uses the same spectrometer optics for the two spectral detection channels and, therefore, achieves better matching between two spectral detection channels and consequently better performance in CCA suppression as compared with the dual spectrometer solution. Full-range imaging with CCA suppression up to ∼25  dB∼25  dB was demonstrated when imaging an attenuated reflector. The efficacy of both CCA and DC suppressions also was validated by imaging the anterior segment of a rat eye ex vivo. The quality of CCA-suppressed images was significantly improved with regard to those obtained with the dual-spectrometer design.